KAJIAN SIFAT FISIKA EMPAT TANAH UTAMA DI SUMATERA BARAT - Yulnafatmawita Yulnafatmawita; Asmar Asmar; Ari Ramayani (Jurnal Solum, 2007)
A research about soil physical study of four main soils found in West Sumatra was conducted in 2006.  The research was aimed to determine some soil physical properties of four soil which are mostly found in West Sumatra.  The four soil orders assessed were Ultisol from Agricultural Expreriment Station Limau Manis, Oxisol from Lubuk Minturun, Entisol from Tabing Kecamatan Koto Tangah Padang, dan Andisol from Bukik Gompong Kabupaten Solok.  The result showed that at the depth of 0-20 cm soil profile.  Ultisol and Oxisol had finer texture than those of Andisol and Entisol.  Andisol was dominated by silt while Entisol was dominated by sand particles.  Andisol had the lowest bulk density and the highest soil organic matter and total porosity.  Soil Organic matter content of Entisol, Oxisol, and Ultisols was low in criteria.  Plant available water (PAW) was higher in Oxisol, then followed by Andisol, Ultisol, and Entisol.Key words: Organic matter, bulk density, texture, porosity, plant available water